Avaliação da eficácia dos tratamentos com a associação de Sulfadiazina, Pirimetamina e Ácido folínico (SPAF), Azitromicina, infusão de Artemisia annua L. e Espiramicina na prevenção da transmissão vertical da toxoplasmose em Calomys callosus (Rodentia: Cricetidae) - Costa, Idessania Nazareth da (2009)
The aim of this study was to verify the efficiency of the treatment with combination of drugs (sulphadiazine, pyrimethamine, and folinic acid- SPFA), azithromycin, Artemisia annua infusion and spiramycin on the prevention vertical transmission of toxoplasmosis in Calomys callosus. Female C. callosus were perorally infected with 20 cysts of Toxoplasma gondii ME-49 strain at the day that a vaginal plug was observed (1st day of pregnancy -dop). Treatment with azithromycin, A. annua infusion and spiramycin started at the 4th dop, while the treatment with drug association started at the 14th dop. Placenta and embryonic tissues were collected for morphological and immunohystochemical analyses, bioassay and PCR from the 15th to 20th dop. No morphological changes were seen in the placenta and embryonic tissues from females treated with SPFA or azithromycin or spiramycin, but embryo atrophy was observed in animals submitted to A. annua infusion treatment. After treatment, parasites were observed in the placenta and fetal (brain and liver) tissues of the animals that were treated with SPFA, A. annua infusion and spiramycin but the number of parasites was lower than in non-treated animals. Parasites were also observed in the placenta of the animals treated with azithromycin, but not in their embryos. Bioassay and PCR results confirmed the immunohistochemical data. In addition bradyzoite immunostaining was observed in placental and fetal tissues of the animals treated with SPAF. In conclusion, the treatment with azithromycin has shown to be more effective to inhibit the vertical transmission of toxoplasmosis in C. callosus.